Simian virus 40 gene A function and maintenance of transformation. - Osborn, M (1975)
Transformants have been isolated after infection of rat embryo cells at 33 C with either wild-type simian virus 40 or with the temperature-sensitive gene A mutants, tsA7 and tsA28. Examination of properties usually associated with transformation such as growth in 1% serum, growth rate, saturation density, and morphology show that these properties are temperature dependent in the tsA transformants characterized, but are not temperature dependent in the wild-type transformants that have been examined. In the most thoroughly characterized tsA transformants the expression of T antigen also appears to be temperature dependent. These data suggest that an active A function is required for the maintenance of transformation in these cells. In the lytic cycle, the A function is involved in the initiation of DNA synthesis. Thus transformation by simian virus 40 may be the direct consequence of the introduction of the simian virus 40 replicon and the presence of its DNA initiator function, which causes the cell to express a transformed phenotype.